METHOD AND SOFTWARE TOOLS FOR AUTHENTICATION KEY GENERATION - TOMUSYAK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The need to ensure secure user authentication in computer systems is an ongoing concern that requires the development of new approaches and technologies. This paper reviews the latest research and publications on this topic, identifying areas where progress has been made and unsolved parts of the problem that require further attention. The objective of this article is to present novel methods and software tools for generating secure authentication keys. The study involved the development of a new approach to generate keys, a system architecture to support the key generation process, and various methods used in key generation. The results of the study demonstrate the efficacy of the developed software tools in generating secure authentication keys. The proposed methods in this research contribute to the ongoing work in the field of computer security by presenting new techniques for generating secure authentication keys. Organizations can adopt these methods to significantly improve the security of their computer systems and safeguard their users’ sensitive information. The paper presents a detailed explanation of the developed approach, including the design and implementation of the key generation system, the architecture of the system, and the methods used to generate keys. The software tools developed through this study are presented in the form of an application, which can be used to generate secure authentication keys. In conclusion, this article highlights the importance of secure authentication key generation and presents a novel approach for generating these keys. The developed software tools represent a significant step forward in the field of computer security, and there is potential for further research and development in this area. The proposed techniques can be adopted by organizations to improve the security of their computer systems, and the results of this study can serve as a basis for further research in the field.